Influence of storage condition on exosome recovery - Lee, Mijung; Ban, Jae-Jun; Im, Wooseok; Kim, Manho (Biotechnology and bioprocess engineering, 2016)
Most of mammalian cells release extracellular vesicles including exosomes which mediate intercellular communication by delivering a variety of molecules. Despite of their importance in normal physiology and disease progression, the standard criteria of storage condition is indefinite and controversial. Therefore, we investigated exosome’s recovery yield and stability by various storage conditions. To investigate the effect of short-term storage temperature on exosome stability, exosomes were incubated at temperatures ranging from -70 to 90°C for 30 min. Immunoblot results showed that all exosome-associated proteins incubated at 90°C were mostly degraded for a short period of time. To examine the effect of long-term storage, isolated exosomes were incubated for 10 days at from -70°C to room temperature (RT), and exosomal protein, RNA and exosome markers were examined. Protein and RNA amounts were most reduced at RT compared with -70 and 4°C. Incubation at 4°C and RT resulted in major loss of CD63, and decreasing level of HSP70 was shown at only RT. In addition, flow cytometry result showed that exosome population became more dispersed after RT incubation for 10 days compared with -70°C incubated or freshly isolated exosomes. In summary, our results indicate that different storage temperature and period influences recovery yield and morphology of exosome, and storage at below -70°C is the favorable condition for preservation of fresh exosomes for clinical application and basic researches.